The Influence of Parental Sexual Education on the Prevention of Sexual Violence in Children: A Systematic Review - Lina Darmayanti Bainuan; Poppy Wijayanti; Nur Aida Yuliana (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Child sexual abuse is a serious form of violence and a major global public health concern. A 2018 survey by the Ministry of Women’s Empowerment and Child Protection reported that 1 in 17 boys and 3 in 5 girls in Indonesia had experienced sexual violence at least once in their lives. This study aims to analyze the influence of parental sexual education on the prevention of sexual violence in children. Subjects and Method: This systematic review was conducted using the PRISMA-ScR checklist. Database searches were performed in PubMed, Scopus, Wiley Online Library, and ScienceDirect for articles published between 2019 and 2022, with all sources accessible free of charge. The search terms used included: sex education to parents about sexual against children, “sex education” AND “parents” OR “sexual abuse” AND “children” OR “sex education” OR “parents” OR “sexual abuse” OR “children.” Selected articles were then critically appraised using the Joanna Briggs Institute (JBI) checklist. Results: From the initial search across the four databases (PubMed, Scopus, Wiley Online Library, and ScienceDirect), a total of 976 articles were identified. After removing three duplicate articles and screening the full texts, 10 articles met the inclusion criteria and were included in this systematic review. Conclusion: This study identified two main themes showing that parental sexual education plays an important role in helping children understand how to protect themselves and recognize different forms and consequences of sexual violence. The results emphasize that clear guidance and regular education from parents are essential to support children in preventing sexual violence.